DUAL OREXIN RECEPTOR ANTAGONIST (DORA) SEBAGAI TERAPI INSOMNIA: SEBUAH TINJAUAN PUSTAKA - Dianda Faradiba Wardani; Oktafany Oktafany; Anisa Nuraisa Jausal; Oktadoni Saputra (Yayasan Nusantara Hasana Berdikari, 2026)
Insomnia affects more than 852 million adults worldwide and 43.7% of individuals aged ≥19 years in Indonesia, highlighting the need for effective and safe therapy. Benzodiazepines and Z-drugs are commonly used but are associated with risks of tolerance and dependence. Dual orexin receptor antagonists (DORAs) have emerged as a more selective therapeutic alternative. A systematic literature review was conducted using PubMed and Google Scholar, focusing on meta-analyses of suvorexant, lemborexant, and daridorexant. Suvorexant improved subjective total sleep time (MD −19.10), subjective time to sleep onset (MD −8.23), and subjective wake after sleep onset (MD −6.45). Lemborexant at doses of 5–10 mg was effective in improving wake after sleep onset (MD −19.90; −22.24) and sleep onset latency (MD −9.23; −12.56). Daridorexant at doses of 25–50 mg reduced wake after sleep onset (MD −0.30; −0.53) and latent persistent sleep (MD −0.30; −0.53). Adverse effects of DORAs include somnolence, daytime sleepiness, fatigue, abnormal dreams, and nasopharyngitis. Overall, DORAs demonstrated significant effectiveness on subjective sleep parameters compared with control groups, with variations in effect size and safety profiles. DORAs may be considered effective and safe treatments for insomnia, with drug and dose selection tailored to clinical needs.